2018
DOI: 10.1007/s40071-018-0195-4
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas salmonicida isolated from wild and farmed fish and invertebrates in Oman

Abstract: Aeromonas salmonicida was isolated from red spot emperor, king soldier bream, white-spotted rabbit fish and tilapia, and an invertebrate (abalone) in Oman during December 2011-May 2012. The cytotoxic enterotoxin ast gene was found widely distributed among the isolates; aerolysin-like protein (act) and the flagellin structural gene lafA less so; and the nuclease gene (nuc) not at all. However, there was not any evidence of pathogenicity among the isolates when tested in laboratory-based experiments using rainbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…A previous study in Croatia found 26 species of A. hydrophila in 336 wild freshwater fish, where only 3.5% showed signs of acute infection ( Topić Popovic et al, 2000 ). A study in Oman has reported A. salmonicida in 9/417 fish with no clinical signs of the disease ( Alghabshi et al, 2018 ). These results support our findings as we report A. hydrophila in trout without signs of clinical infection, contradicting the widely held view that Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Croatia found 26 species of A. hydrophila in 336 wild freshwater fish, where only 3.5% showed signs of acute infection ( Topić Popovic et al, 2000 ). A study in Oman has reported A. salmonicida in 9/417 fish with no clinical signs of the disease ( Alghabshi et al, 2018 ). These results support our findings as we report A. hydrophila in trout without signs of clinical infection, contradicting the widely held view that Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the low quantity of A. salmonicida detected in the different samples examined in the current study should be likewise given importance due to the fact that A. salmonicida is a known aetiologic agent of furunculosis in salmonids including rainbow trout ( O. mykiss ) and coho salmon ( O. kisutch ) and causes ulcer disease in cyprinids and marine flatfish (Austin & Austin, 2016; Lim & Hong, 2020). Interestingly, A. salmonicida strains isolated from wild fish, including red spot emperor ( Lethrinus lentjan ), king soldier bream ( Argyrops spinifer ), white‐spotted rabbit fish ( Siganus canaliculatus ) and one farmed tilapia ( O. niloticus ) in Oman did not show any evidence of pathogenicity when tested in laboratory‐based experiments using rainbow trout and Nile tilapia as experimental animals despite the fact that cytotoxic enterotoxin ast gene was found widely distributed among the isolates examined (Alghabshi, Austin, & Crumlish, 2018). The detection of different virulence factors possessed by the six A. salmonicida isolates recovered from the water, sediment and gills of apparently healthy tilapia in the present study (Table 4) and their concomitant pathogenicity to naïve tilapia is therefore worthy of thorough investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Aeromonas species of bacteria like A. veronii, A. hydrophila, A. salmonicida and A. sobria also cause life intimidating diseases like epidemic septicaemia, furunculosis, ulcer disease and mortality in Nile tilapia, Oreochromis niloticus, blunt snout bream, salmonids, cyprinids, Garra rufa, etc. [39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%